PENGARUH EKSTRAK KUNYIT TERHADAP PERTUMBUHAN TANAMAN SAWI HIJAU DI DESA BINTANG BARU KECAMATAN SUSUA KABUPATEN NIAS SELATAN - Adirman Laia (Universitas Nias Raya, 2023)
Based on the background of the problem, the continuous use of chemical fertilizers can make the soil harden and lose its porosity. In addition, the people in Bintang Baru Village lack understanding of the content of turmeric which can be processed into natural fertilizer for the growth of green mustard plants. This study aims to determine the effect of turmeric extract on the growth of mustard greens. This research uses a type of quantitative research using pure experimental methods (true experiment) and using a completely randomized design trial (CRD). The population of this study was green mustard plants, which totaled 20 polybags of plants with five treatments and four replications. The treatments used were P0 (without turmeric extract), P1 (50 ml), P2 (100 ml), P3 (150 ml) and P4 (200 ml). The results of this research data were analyzed using the SPSS version 20 application which consisted of a normality test, homogeneity test, hypothesis test and follow-up test. Based on the results of this study, the use of turmeric extract can affect the growth of mustard greens, especially in: (1) Increase in the number of leaf blades, (2) Increase in plant stem height. It was concluded that giving turmeric extract to mustard greens is one way to grow naturally and easily available. Suggestions offered by researchers, turmeric extract should be applied and able to improve agricultural quality.